Analysis of the Use of Digital Payment and Service Quality in Increasing Consumer Satisfaction at Ansar 2 Grocery Store with the Application of Digital Era 4.0 Technology - nicky; Tran Le Duyen; Desma Erica Maryati Manik (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to find out how much digital payment and service quality affect consumer satisfaction at Ansar 2 Medan Grocery Store. The research methodology used is a quantitative descriptive method, the unit of analysis in this study is Ansar 2 Medan and the observation unit is the consumer of Ansar 2. The population in this study is consumers from Ansar 2. The technique for determining the number of samples used in this study is the Hair formula. The results of the ttest showed that the Digital Payment variable had a positive and significant effect on Consumer Satisfaction at the Ansar 2 Medan where the tcount (9.355) > ttable (1.9847), the Service Quality variable had a positive and significant effect on Consumer Satisfaction at the Ansar 2 Medan where the tcount (2.842) > ttable (1.9847). The results of the Ftest showed that Fcount (65.117) > Ftable (3.09) which means that the independent variables simultaneously affected the bound variable. The results of the determination coefficient (R2) test showed that 57.3% of the consumer satisfaction variables were influenced by digital payment and service quality while the remaining 42.7% were influenced by other variables.